Emerging Therapies for Stage III Non-Small Cell Lung Cancer: Stereotactic Body Radiation Therapy and Immunotherapy - Kumar, Sameera S.; Higgins, Kristin A.; McGarry, Ronald C. (Frontiers in Oncology, 2017)
The current standard of care for locally-advanced non-small cell lung cancer includes radiation, chemotherapy, and surgery in certain individualized cases. In unresectable non-small cell lung cancer, chemoradiation has been the standard of care for the past three decades. Local and distant failure remains high in this group of patients, so dose escalation has been studied in both single institution and national clinical trials. Though initial studies showed a benefit to dose escalation, phase III studies examining dose escalation using standard fractionation or hyperfractionation have failed to show a benefit. Over the last 17 years, stereotactic body radiation therapy has shown a high degree of safety and local control for stage I lung cancers and other localized malignancies. More recently, phase I/II studies using stereotactic body radiation therapy for dose escalation after conventional chemoradiation in locally-advanced non-small cell lung cancer have been promising with good apparent safety. Immunotherapy also offers opportunities to address distant disease and preclinical data suggests immunotherapy in tandem with stereotactic body radiation therapy may be a rational way to induce an “abscopal effect” although there is little clinical data as yet. By building on the proven concept of conventional chemoradiation for patients with locally-advanced non-small cell lung cancer with a subsequent radiation dose intensification to residual disease with stereotactic body radiation therapy concurrent with immunotherapy, we hope address the issues of metastatic and local failures. This “quadmodality” approach is still in its infancy but appears to be a safe and rational approach to the improving the outcome of non-small cell lung cancer therapy.